Corporate Investment Dynamics: The Effect of Operating Efficiency and Financial Leverage on Capital Expenditure - Md. Adnan Ahmed; Aziza Akhter (Santoso Academy Network, 2025)
This study investigates the effects of operating efficiency and financial leverage on the investment decisions of non-financial listed firms on the Dhaka Stock Exchange, while accounting for factors such as firm age, size, profitability, economic growth, and the impacts of COVID-19. Utilizing a comprehensive dataset that encompasses a wide range of non-financial firms, the analysis applied both the Random Effects model and the Panel-Corrected Standard Errors (PCSE) model to ensure robustness in the results. The findings indicate that both operating efficiency, as measured by asset turnover, and financial leverage significantly influence corporate investment decisions across both models. Notably, firms demonstrating higher operating efficiency are more likely to elevate their capital expenditures, whereas financial leverage tends to have a detrimental effect on corporate investment. Additionally, the analysis of control variables offers further insights into how these factors shape investment behavior. The results highlight the critical role of effective resource management and cautious financial strategies in steering corporate investment decisions. This study enhances our understanding of investment behavior in non-financial firms and points to potential avenues for future research, including the investigation of additional variables and sector-specific analyses.